A novel chaotic image encryption algorithm based on improved baker map and logistic map - Luo, Yuqin; Yu, Jin; Lai, Wenrui; Liu, Lingfeng (Multimedia tools and applications, 2019)
A novel image encryption algorithm based on double chaotic systems is proposed in this paper. On account of the limited chaotic range and vulnerability of a single chaotic map, we use the two-dimensional Baker chaotic map to control the system parameters and the state variable of the logistic chaotic map. After control, the parameter of the logistic map is varying, and the generated logistic sequence is non-stationary. The improved map has been proven to be random and unpredictable by complexity analysis. Furthermore, a novel image encryption algorithm, including shuffling and substituting processes, is proposed based on the improved chaotic maps. Many statistical tests and security analysis indicate that this algorithm has an excellent security performance, and it can be competitive with some other recently proposed image encryption algorithms.